Fraud Perpajakan oleh Petugas Pajak di Indonesia Periode 2021–2025: Analisis Modus, Faktor Penyebab, dan Dampaknya terhadap Kepatuhan Wajib Pajak - Aryanto Nur (CV. ITTC INDONESIA, 2026)
Tax fraud committed by tax officials is a serious problem, resulting in decreased public trust, weakened taxpayer compliance, and disrupted the effectiveness of the tax administration system. In the 2021–2025 period, various fraud cases involving tax officials in Indonesia were exposed to the public, demonstrating weaknesses in individual integrity, internal control, and institutional governance. This study aims to analyze the modus operandi of tax fraud committed by tax officials, examine the factors causing the fraud, and evaluate its impact on taxpayer compliance and public trust. This study uses a qualitative descriptive approach with a case study method. The object of this study is tax fraud committed by tax officials in Indonesia, with a sample size of 2021–2025. This study uses secondary data, with data collection techniques carried out through documentation and literature studies. Data analysis in this study was conducted using qualitative thematic analysis, which includes the following stages: data reduction, categorization and coding, pattern and relationship analysis, and drawing conclusions. The results show that tax fraud is generally carried out through abuse of authority in tax audits, collection, and services, including the practice of gratification, extortion, and manipulation of tax administration. Factors driving fraud include individual pressure, weak internal oversight, a permissive organizational culture, regulatory complexity, and high levels of official discretion. This study concludes that tax fraud negatively impacts taxpayer compliance, particularly voluntary compliance, and undermines public trust in tax institutions. These findings underscore the importance of strengthening internal controls, enforcing ethics among tax officials, and reforming tax institutions as sustainable fraud prevention and control efforts.